STRATEGI PEMBANGUNAN KAWASAN WISATA PANTAI ANGSANA DI KECAMATAN ANGSANA KABUPATEN TANAH BUMBU - Catur Harianto; Ahmad Yunani; Muhammad Riduan Syafari (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2020)
Angsana Beach is one of the beaches in Tanah Bumbu that still needs to be developed for itstourism object because this beach is a relatively new tourist destination, but currently it has begun tobe developed by the Tanah Bumbu regional government and is starting to be visited by many localtourists. The purpose of this study is to determine the potential of tourism development areas in theDistrict of Angsana and the harmonization of regional strategies in developing tourism areas using theprinciple of Bottom Up Planning. This research method uses descriptive qualitative primary data withstructured interviews with local governments, tourism awareness groups (Pokdarwis). The resultsshowed that the Angsana Beach Development which was carried out based on the concept of bottom updevelopment or development from the bottom up, was still ineffective because what had been plannedhad not been realized evenly, because not all of the development programs that had been implementedwere going well. The goal of bottom up development at Angsana Beach is to accelerate the coastaldevelopment process. Regional planning should be carried out in a participatory manner and comefrom below (bottom up planning), that is, starting from the village. In addition, local governments needto design appropriate marketing communications in order to produce regional planning that isappropriate to the local context as well as a participatory regional development planning process thatdeparts from the village. Keyword: Development Strategy, Marketing Communication, BottomUpPlanning, Ecotourism,Angsana Beach, Pokdarwis.